Toxicity assessment of aqueous extracts of ash from forest fires - Silva, Vera
Wildfires can cause immediate and drastic impacts on the structure and functioning of ecosystems, and there has been an increasing interest in wildfire effects on water chemistry and aquatic biota. Wildfires are increasingly recognized as a diffuse source of contamination of aquatic ecosystems, through the production of deleterious pyrolytic substances and their subsequent transport,mostly attached to ashes. To study the deleterious effects of the ash-laden runoff fromburnt areas on water quality, composite ash samples of ashes were collected immediately after a forest fire and then used to prepare aqueous extracts of ash (AEA). The AEAwere analyzedwith respect to a large group of chemical elements and the sixteen prioritized polycyclic aromatic hydrocarbons (PAHs). Ca, S, Mg, K and Na were found to be the principal elements in the AEA, while only two low molecular weight PAHs (phenanthrene and naphthalene) were present in quantifiable amounts. In parallel, an ecotoxicological screening of the AEA was performed with four standard aquatic species from different functional groups and trophic levels. The AEA was found to induce a statistically significant decrease in the growth of two primary producers – Pseudokirchneriella subcapitata and Lemna minor – and inhibited the luminescence of the bacteria Vibrio fischeri. By contrast, AEA did not produce a significant immobilization of Daphniamagna suggesting that short-termacute toxicity may be absent at higher trophic levels. Overall, the present results emphasize the role of wildfires as a potential source of diffuse contamination for downstream water bodies, compromising both chemical and ecological conditions. At the same time, this study highlights the need for further research into the complexity of the potentially deleterious ecological effects of wildfires on aquatic communities, with a particular focus on cascading effects along the trophic web.